The novel LESS (low-cost entrainment syringe system) O2 blender for use in modified bubble CPAP circuits: a clinical study of safety - Wu, Andrew G.; Luch, Sreyleak; Slusher, Tina M.; Fischer, Gwenyth A.; Lunos, Scott A.; Bjorklund, Ashley R. (Frontiers in Pediatrics, 2024)
Background Bubble continuous positive airway pressure (bCPAP) is used in resource-limited settings for children with respiratory distress. Low-cost modifications of bCPAP use 100% oxygen and may cause morbidity from oxygen toxicity. We sought to test a novel constructible low-cost entrainment syringe system (LESS) oxygen blender with low-cost modified bCPAP in a relevant clinical setting. Methods We conducted a clinical trial evaluating safety of the LESS O2 blender among hospitalized children under five years old in rural Cambodia evaluating the rate of clinical failure within one hour of initiation of the LESS O2 blender and monitoring for any other blender-related complications. Findings Thirty-two patients were included. The primary outcome (clinical failure) occurred in one patient (3.1%, 95% CI = 0.1–16.2%). Clinical failure was defined as intubation, death, transfer to another hospital, or two of the following: oxygen saturation <85% after 30 min of treatment; new signs of respiratory distress; or partial pressure of carbon dioxide ≥60 mmHg and pH <7.2 on a capillary blood gas. Secondary outcomes included average generated FiO2's with blender use, which were 59% and 52% when a 5 mm entrainment was used vs. a 10 mm entrainment port with 5–7 cm H2O of CPAP and 1–7 L/min (LPM) of flow; and adverse events including loss of CPAP bubbling (64% of all adverse events), frequency of repair or adjustment (44%), replacement (25%), and median time of respiratory support (44 h). Interpretation Overall the LESS O2 blender was safe for clinical use. The design could be modified for improved performance including less repair needs and improved nasal interface, which requires modification for the blender to function more consistently.